Shilling & Smith acquisition of Xteria Inc. : data center technology leasing - Jeffery, Mark, 1965- (SAGE Knowledge. Cases., 2006)
The Shilling & Smith case examines how to evaluate different lease options when acquiring data center information technology (IT) infrastructure. Specifically, the case addresses software versus hardware leasing, various lease terms, and choosing between different lease structures depending on the strategy and needs of the company. A secondary objective of the case is to teach students the important components of IT infrastructure.